An approach to improve the care of mid-life women through the implementation of a Women's Health Assessment Tool/Clinical Decision Support toolkit. (September 2016) - Silvestrin, Terry M; Steenrod, Anna W; Coyne, Karin S; Gross, David E; Esinduy, Canan B; Kodsi, Angela B; Slifka, Gayle J; Abraham, Lucy; Araiza, Anna L; Bushmakin, Andrew G; Luo, Xuemei
The objectives of this study are to describe the implementation process of the Women's Health Assessment Tool/Clinical Decision Support toolkit and summarize patients' and clinicians' perceptions of the toolkit. The Women's Health Assessment Tool/Clinical Decision Support toolkit was piloted at three clinical sites over a 4-month period in Washington State to evaluate health outcomes among mid-life women. The implementation involved a multistep process and engagement of multiple stakeholders over 18 months. Two-thirds of patients (n = 76/110) and clinicians (n = 8/12) participating in pilot completed feedback surveys; five clinicians participated in qualitative interviews. Most patients felt more prepared for their annual visit (69.7%) and that quality of care improved (68.4%) while clinicians reported streamlined patient visits and improved communication with patients. The Women's Health Assessment Tool/Clinical Decision Support toolkit offers a unique approach to introduce and address some of the key health issues that affect mid-life women.